THE RANGE OF EFFECTIVE IMPACTS ON SOCIETY: A SHIFT OF EMPHASIS - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2026)
The impact on the population of any cultural-civilizational world can be spontaneous or purposefully organized, complex or fragmented-partial, internal or external, have different objectives and nature (in particular, progress or regression; assistance or hindrance to natural transformations; acceleration, deceleration or modification of the process).